Comparing spatial management tools to protect highly migratory shark species in the Eastern Mediterranean Sea hot spots. (1st July 2023) - Zemah-Shamir, Shiri; Zemah-Shamir, Ziv; Peled, Yoav; Sørensen, Ole Johannes Ringnander; Schwartz Belkin, Inbar; Portman, Michelle E.
Abstract: Bycatch of non-target species is a pressing problem for ocean management. It is one of the most concerning issues related to human-wildlife interactions and it affects numerous species including sharks, seabirds, sea turtles, and many critically endangered marine mammals. This paper compares different policy tools for ocean closure management around a unique shark aggregation site in Israel's nearshore coastal waters. We provide a set of recommendations based on an optimal management approach that allows humans to enjoy marine recreational activities such as fishing, while maintaining safe conditions for these apex predators which are vital to the local marine ecosystem. To learn more about recreational fishers' derived benefits, we use a benefit transfer method. Our main conclusion is that dynamic time-area closures offer sustainable and effective management strategies. Since these closures are based on near real-time data, they might successfully preserve specific species in limited areas (i.e., small areas). Highlights: Fisher-shark interactions cause depletion of sharks' population when fishing is allowed The benefit of fisherfolk is reduced when fishing is forbidden Dynamic time-area closures offer a sustainable and effective management strategy Closures based on real-time data may be more effective for some stakeholders than for others